VULPINE VILENESS AND DEMONIC (DAOIST) MAGIC: A RECONSIDERATION OF THE TEXTUAL HISTORY OF SUPPRESSING THE DEMONS. Issue 1 (May 2014) - Yue, Isaac
<x content-type="archive" xml:space="preserve">Abstract</x> This paper aims to re-evaluate our understanding of Suppressing the Demons through the themes of the demonic and the supernatural. The crux of my investigation lies in the text's displacement of Wang Ze from the historical catalyst of the rebellion in 1047, who professed to have gained magical power through Maitreya Buddhism, to the reluctant leader in the novel who is manipulated by the fox demons into leading the rebellion. By looking into the textual history of this novel from a socio-historical perspective, I hope not only to contribute to our knowledge of the cultural significance of such notions as magic and the supernatural during the Ming Dynasty, but more importantly, to re-consider the popular notion that the supernatural elements of the story are a later addition by Feng Menglong (1574–1646) and to shed new light on the textual relationship between the extant twenty- and forty-chapter versions of the novel.